Brief Report: Complete Genome Sequence of CG-0018a-01 Establishes HIV-1 Subtype L. (1st March 2020) - Yamaguchi, Julie; Vallari, Ana; McArthur, Carole; Sthreshley, Larry; Cloherty, Gavin A.; Berg, Michael G.; Rodgers, Mary A.
Abstract : Background: The full spectrum of HIV-1 diversity can be found in Central Africa, including 2 divergent HIV-1 strains collected in 1983 and 1990 in Democratic Republic of Congo (DRC) that were preliminarily classified as group M subtype L. However, a third epidemiologically distinct subtype L genome must be identified to designate L as a true subtype. Methods: Specimen CG-0018a-01 was collected in 2001 in DRC as part of an HIV diversity study. Previous subgenomic HIV-1 sequences from this specimen branched closely with proposed subtype L references. Metagenomic next-generation sequencing (mNGS) and HIV-specific target-enriched (HIV-xGen) libraries were combined for NGS to extend genome coverage. mNGS reads were analyzed for the presence of other coinfections with the sequence-based ultrarapid pathogen identification bioinformatics pipeline. Results: A complete HIV-1 genome was generated with an average coverage depth of 47, 783×. After bioinformatic analysis also identified hepatitis B virus reads, a complete hepatitis B virus genotype A genome was assembled with an average coverage depth of 73, 830×. The CG-0018a-01 HIV-1 genome branched basal to the 2 previous putative subtype L strains with strong bootstrap support of 100. With no evidence of recombination present, the strain was classified as subtype L. Conclusions: The CG-0018a-01 HIV-1 genome establishes subtype L and confirms ongoing transmission in DRC as recently as 2001. Since CG-0018a-01 is more closely related to an ancestral strain than to isolates from 1983 to 1990, additional strains are likely circulating in DRC and possibly elsewhere.